Kearifan Lokal Dan Pendekatan Dalam Pemanfaatan Sumber Daya Alam Untuk Ekonomi Desa Sesaot - Pariani, Lina; Sarjan, Muhammad (Mataram University, 2024)
Local wisdom is a cultural heritage that has been acquired and passed down from generation to generation in a community or society. Local wisdom includes knowledge, values, technology, practices and skills possessed by the community in utilizing the natural resources around them. Wise and sustainable use of natural resources is important in the context of village economic development, especially in Indonesia which has abundant natural wealth. Research Method Observer as an instrument (human instrument) This means that the researcher himself has the function of determining the focus of the research, selecting informants as data sources, carrying out data collection, analyzing data, and making conclusions about his findings. The research results show that local wisdom in the use of natural resources for village economic development, especially in Sesaot Village, West Lombok Regency, West Nusa Tenggara Province, Indonesia. Local wisdom is a cultural heritage that includes knowledge, values, technology, practices and skills passed down from generation to generation in a community. Wise and sustainable use of natural resources is important in the context of village economic development in Indonesia which has abundant natural wealth. The local wisdom approach in the use of natural resources includes the knowledge, practices and expertise possessed by local communities. In Sesaot Village, the community has long developed local wisdom in utilizing the natural resources around them, including in managing forests using a customary system that has existed since their ancestors. By optimizing local wisdom, communities are able to utilize natural resources sustainably while preserving nature through environmentally friendly practices. Utilization of natural resources for village economic development provides many benefits, including increasing income, creating jobs, developing industry, strengthening the local economy, and improving the quality of life of village communities. Political ecology approaches, human welfare ecology, and anthropological perspectives are used to understand and apply local wisdom in environmental management and village economic development